F=jMv2r

Rewrite the equation as jMv2r=F.

jMv2r=F

Multiply both sides of the equation by r.

jMv2=F⋅(r)

Multiply F by r.

jMv2=Fr

Divide each term in jMv2=Fr by jM.

jMv2jM=FrjM

Simplify jMv2jM.

Cancel the common factor of j.

Cancel the common factor.

jMv2jM=FrjM

Rewrite the expression.

Mv2M=FrjM

Mv2M=FrjM

Cancel the common factor of M.

Cancel the common factor.

Mv2M=FrjM

Divide v2 by 1.

v2=FrjM

v2=FrjM

v2=FrjM

v2=FrjM

Take the square root of both sides of the equation to eliminate the exponent on the left side.

v=±FrjM

Simplify the right side of the equation.

Rewrite FrjM as FrjM.

v=±FrjM

Multiply FrjM by jMjM.

v=±FrjM⋅jMjM

Combine and simplify the denominator.

Multiply FrjM and jMjM.

v=±FrjMjMjM

Raise jM to the power of 1.

v=±FrjMjMjM

Raise jM to the power of 1.

v=±FrjMjMjM

Use the power rule aman=am+n to combine exponents.

v=±FrjMjM1+1

Add 1 and 1.

v=±FrjMjM2

Rewrite jM2 as jM.

Use axn=axn to rewrite jM as (jM)12.

v=±FrjM((jM)12)2

Apply the power rule and multiply exponents, (am)n=amn.

v=±FrjM(jM)12⋅2

Combine 12 and 2.

v=±FrjM(jM)22

Cancel the common factor of 2.

Cancel the common factor.

v=±FrjM(jM)22

Divide 1 by 1.

v=±FrjMjM

v=±FrjMjM

Simplify.

v=±FrjMjM

v=±FrjMjM

v=±FrjMjM

Combine using the product rule for radicals.

v=±FrjMjM

v=±FrjMjM

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

v=FrjMjM

Next, use the negative value of the ± to find the second solution.

v=-FrjMjM

The complete solution is the result of both the positive and negative portions of the solution.

v=FrjMjM

v=-FrjMjM

v=FrjMjM

v=-FrjMjM

v=FrjMjM

v=-FrjMjM

Solve for v F=(jMv^2)/r